Investigating the farmers’ perception towards the creation and development of diversification components in economic activities: the case of rural areas of Baghlan Jadid district of Baghlan province-Afghanistan - Shaiq, Muhammad Asef; Hashemi, Sayed Reza; Hashemi, Said Ahmad Asim (Journal of Agriculture and Environment for International Development (JAEID), 2024)
Developing economic activities in villages has been known as one of the important approaches to poverty reduction, entrepreneurship development, and sustainable development of the rural economy. The most important feature of the Afghanistan villages’ economic structure is the lack of diversity in economic platforms as well as the lack of employment opportunities. In this regard, the present study was conducted to identify the components of the creation and development of diversification to rural economic activities and provide solutions in this context in the villages of the Baghlan Jadid district of Baghlan province. The statistical population for this research was all farmers of the Baghlan Jadid district. In this research, the sample size was determined using Cochran’s formula of 363 people, which was done by multi-stage sampling method. The data collection tool was a questionnaire and the method was a face-to-face interview. Coefficient of Variation and Exploratory Factor Analysis was used to analyze and describe the data, in addition to descriptive statistics of centrality and dispersion. The results of the factor analysis showed that the components of "education-empowerment", "supporting component", "infrastructure-facilities component", "strategic-legal component" and "access to market component" are considered to be the most important components of creating and developing diversification in rural economic activities, respectively. Also, the findings of the study showed that the villages of this district have the potential capabilities, such as the presence of water resources such as springs and rivers for fish farming, the existence of beautiful landscapes and green spaces, the presence of the spirit of hospitality among the villagers and the belief of the villagers in the employment and income generation of non-agricultural activities. The findings of this innovative study, while facilitating the involvement of villagers in rural economic activities, can also be useful for policymakers and planners in this field.